Ticagrelor in patients with heart failure after acute coronary syndromes: Insights from the PLATelet inhibition and patient Outcomes (PLATO) trial - Åkerblom, Axel; Katus, Hugo (American heart journal, 2019)
Background - Heart failure (HF) following acute coronary syndromes (ACS) is associated with worse prognosis; however, the efficacy and safety of ticagrelor in patients with HF and if ticagrelor influences the risk of new-onset HF are unknown. - Methods - We examined the efficacy and safety of ticagrelor compared to clopidogrel in patients with ACS in the randomized PLATelet inhibition and patient Outcomes (PLATO) trial subdivided by strata: (1) previous HF and/or clinical signs of HF on admission or (2) no HF on admission. The primary outcome was the combination of cardiovascular death, myocardial infarction, or stroke evaluated by multivariable Cox regression models. The safety outcome was major bleeding. New-onset HF was defined as an HF event after discharge in patients without previous HF. - Results - Data were available in 18,556 patients, whom 2,862 (15.4%) patients had HF, including 1,584 (8.5%) patients with previous HF. Patients randomized to ticagrelor had lower risk of the composite end point regardless of HF status: hazard ratio (HR) 0.87 (95% CI: 0.73-1.03) in patients with HF and HR 0.84 (95% CI: 0.75-0.93) in patients with no HF (P=.76). Corresponding HR for major bleeding were HR 1.08 (95% CI: 0.87-1.34) and HR 1.03 (95% CI: 0.94-1.14) (P=.71). There was no difference in new-onset HF at 12months between patients randomized to ticagrelor (4.1%, n=278) or clopidogrel (4.0%, n=276). - Conclusions - In patients with ACS, ticagrelor is more efficacious in protecting against new ischemic events and mortality than clopidogrel irrespective of the presence of HF. There is no difference between ticagrelor or clopidogrel treatment in new-onset HF post-ACS.
Gesehen am 23.10.2019